FACTORS AFFECTING THE TURKSIH FARMERS’ DECISION TO QUIT FARMING - Berna TÜRKEKUL; Canan ABAY (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Agriculture contributes to Turkish economic development by manufacturing essential agricultural products, utilizing a huge portion of the population, trading of agricultural products, making intermediate goods for the other sectors. However, poverty along with deepening gap between input and output prices caused by Turkish agricultural policies implemented in the recent years has pushed farmers to quit farming. As a matter of fact, in 2017 5.4 million worked in agricultural sector, which were 7.7 million people in 2000. Therefore, object of this study was to investigate the factors affecting farmers’ likelihood to quit agriculture. The data was collected by a questionnaire conducted in the selected districts of Izmir and totally 195 farmers are calculated as sample size. Logit regression model was used to determine the factors affecting quitting agriculture. The results show that agricultural subsidy, tenure, education and the size of the farm are the important factors for quitting decision. The question of who will make agricultural production in the future will be on the agenda as long as agriculture loses attractiveness for young people. The situation is no different in a country with a high young population country like Turkey. Hence, agriculture should be encouraged especially for young people with high education and entrepreneurship ability.